Teaching traffic safety in Qatari schools: Expectation and reality - Ebtisam Naji (19794264) (2015)
Introduction In pursuit of the realization of the Qatar National Vision 2030 (QNV 2030) and to ensure the success of the hosting of the 2022 FIFA World Cup, the Qatari higher authorities have assigned paramount importance to instilling and prorogating traffic awareness among the various community groups and school students. Thus, the establishment of the National Committee for Traffic Safety (NCTS) headed by His Excellency the Prime Minister and Minister of Interior in which the relevant authorities in Qatar have been accomplished. The National Committee for Traffic Safety has prepared a general educational framework for traffic safety program, familiarizing students of all age groups with many of the traffic safety concepts to ensure instilling the needed traffic awareness. This study aims at identifying the effectiveness of the application of the general educational framework of the traffic safety program on experimental basis in some governmental and private schools in Qatar (2015-2013) in preparation to introducing it to all schools in the coming years (if the outcome of the pilot project is proved positive). Study Approach This study will be made as part of the assessment of the implementation of the procedural action plans for teaching traffic safety in Qatar. The study will include conducting a survey among school principals, teachers, parents and students, and measuring the impact of the acquisition of traffic safety knowledge on the students› behavior by examining the school zones and how far the traffic safety measures are applied. It will also follow-up the extra-curricular activities carried out by students outside the classroom. Study Expectations The results of this study are expected to contribute to the enhancement and improvement of the general framework of the proposed educational content before its application on all Qatari schools. As expected in this study, many government and private entities are to be engaged in the preparation of the teaching aids and awareness films to ensure the effective application of the traffic safety concepts on schools. It is also expected that the development of the framework would include the following aspects: preparation of teaching aids, production of awareness films appropriate for each age group and preparation of illustrative pictures and workshops designed to educate teachers before the application of the educational framework. It also aims to improve school zones to enhance traffic safety around schools in accordance with the international safety standards and measures among other improvements. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.54